2016
DOI: 10.3892/ijo.2016.3744
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17 promotes epithelial-mesenchymal transition via TGF-β/Smad pathway in gastric carcinoma cells

Abstract: Although a disintegrin and metalloproteinase-17 (ADAM17) overexpression has been demonstrated in numerous human tumors including gastric cancer, its role in gastric cancer development remains to be clarified. In the present study, we identify that ADAM17 activates TGF-β/Smad signaling to promote epithelial-mesenchymal transition (EMT) in gastric cancer cells. We found that ADAM17 promotes proliferation, migration and invasion in gastric carcinoma cells. Subsequently, we revealed that silencing ADAM17 induces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…While overexpression of members of the disintegrin and metalloprotease (ADAM) family has been widely documented in cancers and invasion [ 3 ], few have been directly involved in EMT. SiRNA-based knockdown of ADAM9 in pancreatic cancer cells has been shown to diminish cellular migration, invasion, and to induce the epithelial marker E-cadherin [ 4 ] and a role of ADAM17 in promoting EMT has been recently reported in lung adenocarcinoma cells [ 5 ] and gastric carcinoma cells [ 6 ]. The association of ADAM12 with breast cancer aggressiveness and EMT has been suggested by several lines of evidence that include the ability of ADAM12-overexpressing breast cell lines to induce metastasis in vivo [ 7 , 8 ] and its correlated expression with the presence of metastases in triple-negative breast cancer [ 9 ] and with a breast tumor-initiating cell phenotype [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While overexpression of members of the disintegrin and metalloprotease (ADAM) family has been widely documented in cancers and invasion [ 3 ], few have been directly involved in EMT. SiRNA-based knockdown of ADAM9 in pancreatic cancer cells has been shown to diminish cellular migration, invasion, and to induce the epithelial marker E-cadherin [ 4 ] and a role of ADAM17 in promoting EMT has been recently reported in lung adenocarcinoma cells [ 5 ] and gastric carcinoma cells [ 6 ]. The association of ADAM12 with breast cancer aggressiveness and EMT has been suggested by several lines of evidence that include the ability of ADAM12-overexpressing breast cell lines to induce metastasis in vivo [ 7 , 8 ] and its correlated expression with the presence of metastases in triple-negative breast cancer [ 9 ] and with a breast tumor-initiating cell phenotype [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that approximately 28,000 newly diagnosed cases and 10,960 deaths will occur in the United States in 2017 [ 2 ]. Although diagnostic and therapeutic techniques of GC have made advances over the past decades, the mortality rate is still fairly high due to its aggressive behavior [ 3 6 ]. Thus, a number of researchers have focused on probing several molecular biomarkers to modify clinical management strategies and better understand the molecular mechanism of GC [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 In gastric carcinoma, ADAM17 promoted epithelial-mesenchymal transition via TGF-β/Smad pathway. 29 These data suggested that ADAM17 may promote cancer progression through affecting cell growth and invasion. A previous study confirmed that overexpression of ADAM17 contributed to OSCC development and targeting ADAM17 may be a potential therapeutic target in OSCC.…”
Section: Discussionmentioning
confidence: 95%